EVALUATION OF THE PHYSIOLOGICAL POTENTIAL OF Panicum maximum SEEDS BY MULTIVARIATE ANALYSIS - Pereira, Francisco Elder Carlos Bezerra; Jeromini, Tatiane Sanches; da SILVA, Givanildo Zildo; Torres, Salvador Barros; Martins, Cibele Chalita [UNESP] (PPUFU - Portal de Periódicos da Universidade Federal de Uberlândia, 2022)
The aim of this work was to identify efficient vigor tests for differentiating the seed lots, forecasting seedling emergence in the field and assessing the physiological quality of Panicum maximum seeds. 12 seed lots from the cultivar Tanzania and 11 seed lots from the cultivar Massai were evaluated for water content, germination, first count and germination speed index, emergence and first emergence count of seedlings in sand, root length and shoot length, analysis of SVIS® images (seedling length, vigor and uniformity index) and seedling emergence in the field. The work was conducted in a completely randomized design for tests performed in the laboratory and in randomized blocks for tests in the field. The data were subjected to analysis of variance and the means compared by Scott Knott's test at 5% probability and statistical multivariate clustering analysis and principal components analysis. The shoot and root length tests are efficient for the evaluation of the physiological potential of P. maximum cv. Massai, while the seedling length, vigor index and growth uniformity index tests using image analysis, seedling emergence in sand and first seedling emergence count in sand are efficient in assessing the physiological potential of seeds of P. maximum cv. Tanzania, and providing information similar to that of seedling emergence in the field.
Keywords: Image Analysis; Massai Grass; Multivariate Statistics; SVIS®; Tanzania Grass